2017
DOI: 10.3390/su9040625
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Household Waste Separation Behaviour: Testing the Roles of Moral, Past Experience, and Perceived Policy Effectiveness within the Theory of Planned Behaviour

Abstract: Due to the increasing waste generation over the years in China, there is an urgent need to addressing this major problem by implementing effective household waste separation programs. Although past studies have tried to explain the waste behaviour from social and psychological motivations, there is little understanding as to the impact of individual moral obligation and past experience on forming waste separating intention. The aim of this study is to investigate key determinants influencing household waste se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
176
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 78 publications
(84 reference statements)
13
176
0
8
Order By: Relevance
“…Although Tonglet et al [18] and Xu et al [21] suggest the inclusion of additional independent constructs, such as moral norm, past experience and perceived consequences of recycling, we found the original framework of the TPB sufficient to address our main question about the relative effects of social as opposed to spatial and physical factors. Thus, the core constructs of 'attitude', 'social norm', and 'PBC' allowed sufficient differentiation between the effects of social as opposed to spatial and physical factors, provided we were able to adopt a wider conceptualisation of PBC to include situational factors such as storage space and access to recycling facilities [23].…”
Section: Theoretical Frameworkmentioning
confidence: 87%
See 1 more Smart Citation
“…Although Tonglet et al [18] and Xu et al [21] suggest the inclusion of additional independent constructs, such as moral norm, past experience and perceived consequences of recycling, we found the original framework of the TPB sufficient to address our main question about the relative effects of social as opposed to spatial and physical factors. Thus, the core constructs of 'attitude', 'social norm', and 'PBC' allowed sufficient differentiation between the effects of social as opposed to spatial and physical factors, provided we were able to adopt a wider conceptualisation of PBC to include situational factors such as storage space and access to recycling facilities [23].…”
Section: Theoretical Frameworkmentioning
confidence: 87%
“…Ajzen's [17] Theory of Planned Behaviour (TPB) is a widely used framework for studying environmental behaviour, including recycling [18][19][20][21]. According to the TPB, three factors (independent constructs) guide human behaviour (the dependent construct), including 'attitude' towards a certain behaviour (i.e., beliefs about the consequences of performing the behaviour), 'subjective norm' (i.e., perception of others' expectations of one to perform the behaviour, notably social pressure), and 'perceived behavioural control' (PBC) (i.e., how much control one believes one has to perform the behaviour, notably the ability to perform the behaviour).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Some studies on recycling include additional determinants, such as moral norm, past experience and perceived consequences of recycling [25,28]. We found the original framework of the TPB sufficient to address our main question about the overall effect of a recycling service on recycling behaviour in a security development.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…We used Ajzen's [24] well-known Theory of Planned Behaviour (TPB) as a theoretical framework considering its applicability to environmental behaviour, especially recycling [25][26][27][28]. According to the TPB, there are three determinants of behaviour, including 'attitude' towards the behaviour (i.e., perceptions about the consequences of performing the behaviour), 'subjective norm' (i.e., perceptions of others' expectations to perform the behaviour, notably social pressure), and 'perceived behavioural control' (PBC) (i.e., perceptions of how much control one has to perform the behaviour, notably the ability to perform the behaviour).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In other words, a person's understanding of good and bad can lead them to make either a positive of negative assessment of which behavior to show (Yuang et al, 2016). Xu et al (2017) explain that moral factors often encourage people to be kind to the environment. Bozaci (2014) carried out research which revealed a close connection between morality and green consumption behaviors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%